Identity and rationality in Sharia economic practice: A study at Arrahmah Sharia Consumer Cooperative, South Kalimantan Province - Hafizah, Yulia; Nilasari, Erissa; Syarqawie, Fitriana; Jahra, Pati Matu; Noorwahidah, Noorwahidah (Journal of Islamic Economics Lariba, 2024)
IntroductionThe Sharia consumer cooperative is one of the many legal forms of Islamic economic activity in Indonesia, including South Kalimantan Province. However, studies on the identity and rationality of this practice are still limited.ObjectivesThis research aims to understand how Islamic identity influences economic decisions and how Sharia economic rationality is reflected in the practices of consumer cooperatives. The selection of Arrahmah Sharia Consumer Cooperative (Koperasi Konsumen Syariah Arrahmah) as the subject of the study is based on the institution's claim to be "more Sharia" compared to other cooperatives or Sharia financial institutions.MethodA qualitative research method was employed using in-depth interviews and observations as data collection tools. Qualitative research was chosen for its relevance to case studies that required in-depth data exploration.ResultsThe findings indicate that Islamic identity plays a key role in shaping the economic preferences of cooperative members, whereas Sharia economic rationality is reflected in the principles of justice and sustainability. In the context of Arrahmah Sharia Consumer Cooperative, the institution's assertion of being "more Sharia" is driven by knowledge of fiqh muamalah, particularly the section on usury and its dangers conveyed by Salafi scholars in study forums, websites, and other mass media. This knowledge serves as the main foundation and source of community identity, which distinguishes them from other cooperatives or financial institutions.ImplicationsThe success of Sharia economics lies not only in economic rationality, but also in the understanding and application of religious identity in every aspect of economic activities. Both are complementary and mutually supportive in achieving sustainable economic development goals, in line with religious values.Originality/NoveltyThis study provides insights into the dynamics of identity and rationality in the context of Sharia economics, focusing on the practices of consumer cooperatives in South Kalimantan.